ANALISIS KONTINUITAS EKSPRESI KEAGAMAAN MASYARAKAT KOTA PALEMBANG PADA ERA 1990-AN DAN ERA GLOBALISASI - Dewi, Rusmala (Universitas Islam Negeri Raden Fatah Palembang, 2018)
Abstract The city of Palembang experienced a slow growth process of the city below 1990. In the globalization era, the social mobility process experienced by the people of Palembang city gave birth to a new class in the society which allegedly would later change the religious expression. Therefore, the problems in research are: how the development of religious expression of Palembang city community in the era of the 1990s. Second; whether that led to changes in religious expression in the city of Palembang from the era of the 1990s to the current era of globalization. The development of religious expression of Palembang people in the 1990s can be seen from the background of the understanding of the religion which is the embryo of Islamic history entering Palembang, then the background of social change by showing the religious social behavior of paradox, and the last condition of economic growth rate. While the cause of changes in religious expression in the city of Palembang from the era of the 1990s to the era of globalization today is caused by several factors behind the emergence of change and continuity of religious expression of the city of Palembang is caused by two things: first; intellectual shift of moslem society of Palembang city; and second; collide with the flow of globalization within the city of Palembang. Keywords: Continuity, Community of Palembang City, and Globalization.